2020
DOI: 10.1002/smll.202001325
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption‐Free Growth of Ultra‐Thin Molybdenum Membranes with a Low‐Symmetry Rectangular Lattice Structure

Abstract: Although low‐symmetry lattice structure of 2D transition metals is highly anticipated for both fundamental research and potentially distinctive application, it still has not been experimentally realized, which greatly hinders the exploration of the unique properties. Here, ultra‐thin body‐centered‐cubic (bcc) phase molybdenum (Mo) membranes are successfully synthesized with a low‐symmetry rectangular (110) crystal face via an adsorption‐free reaction. Through experimental and density functional theory studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Researches in two-dimensional (2D) materials have increasingly grown triggered by pioneering studies on graphene [1][2][3][4]. As an emerging family of 2D materials, 2D transition metal phosphides (TMPs) are predicted with novel properties, which are appealing for many applications, including optical, thermal insulating materials, magnetic material and catalysts [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Researches in two-dimensional (2D) materials have increasingly grown triggered by pioneering studies on graphene [1][2][3][4]. As an emerging family of 2D materials, 2D transition metal phosphides (TMPs) are predicted with novel properties, which are appealing for many applications, including optical, thermal insulating materials, magnetic material and catalysts [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of controllable methods for tuning the properties of 2D materials by either reducing their size or creating new nanostructured materials is pivotal to the realization of nextgeneration functional devices. Si et al [43] used an aberrationcorrected TEM system operating at voltages higher than 80 kV to preferentially remove C from 2D 𝛼-Mo 2 C crystals. The irradiation process led to the formation of thin rectangular Mo structures with lattice parameters of 0.233 and 0.167 nm, as shown in Figure 6n and having the (110) crystal orientation.…”
Section: In-situ Electron-beam-driven Thinning and Restructuring As Means Of Forming Suspended 2d Metals/metallenesmentioning
confidence: 99%
“…In addition, while in the case of other methods for synthesizing 2D metals/metal oxides, it may be challenging to demonstrate the freestanding structure of the synthesized material; this difficulty can be overcome using in‐situ (S)TEM ( Figure 1 ) and graphene pores as templates [ 19 , 24 , 36 , 37 , 38 , 39 , 40 ] or e‐beam‐based thinning methods. [ 41 , 42 , 43 , 44 ] In this review, we summarize the recent progress made in the in situ e‐beam‐driven synthesis of freestanding 2D metal/metal oxide membranes using(S)TEM and highlight the importance of in situ (S)TEM in the development of freestanding 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group revealed that ultrathin Mo membranes with a low‐symmetric rectangular (110) crystal face could be synthesized successfully by an adsorption‐free reaction (Figure 6e). [ 17 ] It is the first time that the low‐symmetry lattice structure of 2D transition metals has been experimentally realized, although the rectangular lattice structure exists some transition metals crystal faces. Image simulations verify that the obtained rectangular lattice structure is AB stacked Mo(110) with even atom thickness (2, 4, etc.…”
Section: Synthetic Strategies Of Unconventional Structuresmentioning
confidence: 99%
“…Hitherto, many researchers have made tremendous efforts to synthesize elemental 2D materials with unconventional structures and developed a series of strategies, including surface modification, epitaxial growth, electron beam irradiation, crystal inhibition, and high pressure. [ 13–18 ] However, present scientific achievements and systematic understanding of effective synthetic strategies have not been presented yet. It is highly demanded to give a clear guideline of the different strategies for controlling the preparation and reasonable design of unconventional structures of elemental 2D materials.…”
Section: Introductionmentioning
confidence: 99%